2007
DOI: 10.1093/jaoac/90.2.427
|View full text |Cite
|
Sign up to set email alerts
|

Extractability, Stability, and Allergenicity of Egg White Proteins in Differently Heat-Processed Foods

Abstract: Hen's egg white protein is a major cause of food allergy, and a considerable number of countries have introduced labeling directions for processed food products. To control compliance with these regulations, analytical assays for the detection of egg in manufactured foods have been developed. In this study, we have tested the performance of 3 commercially available kits for quantitative egg analysis using 6 model heat-processed foods. The 3 assays worked well under standard conditions with soluble egg white pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 1 publication
4
25
0
Order By: Relevance
“…However, SDS alone did not increase protein extractability from boiled egg and fried noodle except in the presence of 2-mercaptoethanol (Watanabe et al, 2005). In addition, different researchers have reported that the extraction buffer supplied with the Morinaga ELISA kit, containing both surfactant and reducing agent, helps improve the recovery of egg soluble proteins from thermally processed raw materials and from different food matrices (Fieste, Lovberg, Lindvik & Ecaas, 2007, Fu, Maks & Banaszewski, 2010.…”
Section: Discussionmentioning
confidence: 99%
“…However, SDS alone did not increase protein extractability from boiled egg and fried noodle except in the presence of 2-mercaptoethanol (Watanabe et al, 2005). In addition, different researchers have reported that the extraction buffer supplied with the Morinaga ELISA kit, containing both surfactant and reducing agent, helps improve the recovery of egg soluble proteins from thermally processed raw materials and from different food matrices (Fieste, Lovberg, Lindvik & Ecaas, 2007, Fu, Maks & Banaszewski, 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding lysozyme, heat treatment only showed partial reduction in its allergenicity (Mine & Zhang, 2002;Ouahidi, El Hamsas, & Aarab, 2011). Wheat-containing food showed a stronger lysozyme band in western-blot results, indicating that cooking together with wheat flour, lysozyme increases its IgE-binding capacity (Faeste, Løvberg, Lindvik, & Egaas, 2007). Heat treatment was reported to reduce the allergenicity of ovomucoid and ovalbumin in vivo (Golias et al, 2012;Martos, Lopez-Exposito, Bencharitiwong, Berin, & Węgrzyn, 2011;Rupa, Schnarr, & Mine, 2015).…”
Section: Concise Reviews and Hypotheses In Food Sciencementioning
confidence: 99%
“…Regarding lysozyme, heat treatment only showed partial reduction in its allergenicity (Mine & Zhang, 2002; Ouahidi, El Hamsas, & Aarab, 2011). Wheat‐containing food showed a stronger lysozyme band in western‐blot results, indicating that cooking together with wheat flour, lysozyme increases its IgE‐binding capacity (Faeste, Løvberg, Lindvik, & Egaas, 2007).…”
Section: Effect Of Processing On Allergenicity Of Eggmentioning
confidence: 99%
“…Recently, studies have been conducted to evaluate the performance of the ELISAs in detecting allergenic residues in heat‐processed foods (Williams and others 2004; Fæste and others 2007). However, no studies have been done to evaluate the reliability of these ELISAs in the detection of residues of allergenic foods in the acidic food matrices.…”
Section: Introductionmentioning
confidence: 99%